Socially Useless Jobs - Robert A. J. Dur; Max van Lent (Tinbergen Institute, 2018)
It has been claimed that many workers in modern economies think that their job is socially useless, i.e. that it makes no or a negative contribution to society. However, the evidence so far is mainly anecdotal. We use a representative dataset comprising 100,000 workers from 47 countries at four points in time. We find that approximately 8% of workers perceive their job as socially useless, while another 17% are doubtful about the usefulness of their job. There are sizeable differences between countries, sectors, occupations, and age groups, but no trend over time. A vast majority of workers cares about holding a socially useful job and we find that they suffer when they consider their job useless. We also explore possible causes of socially useless jobs, including bad management, strict job protection legislation, harmful activities at work, labor hoarding, and division of labor.
Keywords: J2; J3; J4; J8; M5; 330; work motivation; job satisfaction; job search; management quality; job protection legislation; sin industries; labor hoarding; division of labor